Transparansi Pelayanan Pengurusan Surat Keterangan Usaha di Kelurahan Sudiang Raya Kecamatan Biringkanaya Kota Makassar - Ambo Masse (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The transparency of business certificates is a crucial aspect for business owners, particularly in terms of openness in public services, as is the case in Sudiang Raya Village, Biringkanaya District, Makassar City. This research is qualitative, with a population of 30 people and a sample of 10 people. The findings indicate that there are still constraints regarding the transparency of service and the accuracy of business certificate completion, with services often not being completed on time. These delays and inefficiencies impact the trust of business owners and hinder the smooth operation of businesses. Therefore, it is essential for the Sudiang Raya Village Government to emphasize the importance of adhering to official rules and procedures to ensure that business certificate services are provided consistently, equitably, and within the expected timelines. Furthermore, clear communication and proper monitoring of the service process are needed to address the gaps identified in this study. Ensuring transparency in these services will foster a more conducive business environment, increase satisfaction among business owners, and enhance the overall effectiveness of public service delivery in the village.